New Zinc-Based Active Chitosan Films: Physicochemical Characterization, Antioxidant, and Antimicrobial Properties - Policastro, Debora; Giorno, Eugenia; Scarpelli, Francesca; Godbert, Nicolas; Ricciardi, Loredana; Crispini, Alessandra; Candreva, Angela; Marchetti, Fabio; Xhafa, Sonila; De Rose, Renata; Nucera, Antonello; Barberi, Riccardo C.; et al. (Frontiers in Chemistry, 2022)
The improvement of the antioxidant and antimicrobial activities of chitosan (CS) films can be realized by incorporating transition metal complexes as active components. In this context, bioactive films were prepared by embedding a newly synthesized acylpyrazolonate Zn(II) complex, [Zn(QPhtBu)2(MeOH)2], into the eco-friendly biopolymer CS matrix. Homogeneous, amorphous, flexible, and transparent CS@Znn films were obtained through the solvent casting method in dilute acidic solution, using different weight ratios of the Zn(II) complex to CS and characterized by powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared (FT-IR), Raman, and scanning electron microscopy (SEM) techniques. The X-ray single-crystal analysis of [Zn(QPhtBu)2(MeOH)2] and the evaluation of its intermolecular interactions with a protonated glucosamine fragment through hydrogen bond propensity (HBP) calculations are reported. The effects of the different contents of the [Zn(QPhtBu)2(MeOH)2] complex on the CS biological proprieties have been evaluated, proving that the new CS@Znn films show an improved antioxidant activity, tested according to the DPPH method, with respect to pure CS, related to the concentration of the incorporated Zn(II) complex. Finally, the CS@Znn films were tried out as antimicrobial agents, showing an increase in antimicrobial activity against Gram-positive bacteria (Staphylococcus aureus) with respect to pure CS, when detected by the agar disk-diffusion method.